Short review of Siberian Parnassius apollo Linnaeus, 1758 with the description of the new subspecies and designation of the neotype of P. a. sibiricus (Nordmann, 1851) (Lepidoptera, Papilionidae) - Sergei V. Churkin; Roman V. Yakovlev (Acta Biologica Sibirica)
The paper presents a short review of Parnassius apollo Linnaeus, 1758 from East Siberia and Mongolia. One new subspecies is described: P. a. yenisei ssp. nova (type locality: Siberia, Irkutsk region, Uda river, Nizhneudinsk town vic.). The neotype of P. a. sibiricus (Nordmann, 1851) is designated from the vicinity of Irkutsk. The distinctions and relations of the new subspecies are discussed with new data about the synonymy for the Siberian apollo-representatives. New synonymies are established: Doritis apollo L. var. sibirica Nordmann, 1851 [Parnassius apollo sibiricus (Nordmann, 1851)] = Parnassius apollo pseudosibiricus Bryk et Eisner, 1938, syn. n., Doritis apollo L. var. hesebolus Nordmann, 1851 [Parnassius apollo hesebolus (Nordmann, 1851)] = P. apollo tshikoiensis Möhn, 2003 syn. n., Parnassius apollo tannuensis Möhn, 2003 = Parnassius apollo hirschfeldi Möhn, 2003, syn. n.